Time Dependent Collisional‐Radiative Model for Scrape‐Off Layer Impurity Turbulent Transport Studies. Issue 4 (June 2014) - Guzmán, F.; Marandet, Y.; Moulton, D.; Futtersack, R.; Ghendrih, Ph.; Guirlet, R.; Rosato, J.; Stamm, R.; Tamain, P.
Abstract The effects of Scrape‐off layer (SOL) turbulent fluctuations on the ionization/recombination source terms in the continuity equations for impurities are investigated. These effects come in addition to those related to turbulent transport, and could be important in the SOL owing to the large relative fluctuation levels measured there. Given the time scales involved, the ionization balance does not follow adiabatically fluctuations. In order to investigate these effects, we have developed a time dependent solver for the population kinetics of the full atomic system. A first calculation is performed for beryllium, using turbulent fields from the TOKAM2D non isothermal code. Turbulent fluctuations are shown to shift substantially the abundances of the different ionization stages via source averaging effects. A stochastic model, which could potentially be used to generate fluctuation averaged ionization/recombination rate coefficients, is then used to model the output of TOKAM2D. The results for abundances are compared to those of the population kinetics code. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)